Anesthetic management of acute nasal epistaxis occurring during general anesthesia. Issue 8 (27th June 2019) - Chandrakantan, Arvind; Mohammad, Shazia; Adler, Adam C.
Abstract: Spontaneous epistaxis under general anesthesia is a rare untoward event. Typically, mild epistaxis occurs from a nasal airway manipulation and usually resolves spontaneously or with external pressure to the affected nares for a short period of time. In case of epistaxis that is difficult to control with pressure or oxymetazoline, thorough evaluation should be considered. We present a case of a 12‐year‐old experiencing spontaneous nasal bleeding upon emergence difficult to control with noninvasive methods and required intervention by otolaryngology.